RHEB: a potential regulator of chondrocyte phenotype for cartilage tissue regeneration. (6th April 2016) - Ashraf, S.; Ahn, J.; Cha, B.‐H.; Kim, J.‐S.; Han, I.; Park, H.; Lee, S.‐H.
Abstract: As articular cartilage has a limited ability to self‐repair, successful cartilage regeneration requires clinical‐grade chondrocytes with innate characteristics. However, cartilage regeneration via chondrocyte transplantation is challenging, because chondrocytes lose their innate characteristics during in vitro expansion. Here, we investigated the mechanistic underpinning of the gene Ras homologue enriched in brain ( RHEB ) in the control of senescence and dedifferentiation through the modulation of oxidative stress in chondrocytes, a hallmark of osteoarthritis. Serial expansion of human chondrocytes led to senescence, dedifferentiation and oxidative stress. RHEB maintained the innate characteristics of chondrocytes by regulating senescence, dedifferentiation and oxidative stress, leading to the upregulation of COL2 expression via SOX9 and the downregulation of p27 expression via MCL1. RHEB also decreased the expression of COL10 . RHEB knockdown mimics decreased the expression of SOX9, COL2 and MCL1, while abrogating the suppressive function of RHEB on p27 and COL10 in chondrocytes. RHEB‐overexpressing chondrocytes successfully formed cartilage tissue in vitro as well as in vivo, with increased expression of GAG matrix and chondrogenic markers. RHEB induces a distinct gene expression signature that maintained the innate chondrogenic properties over a long period. Therefore, RHEB expression represents a potentially useful mechanism in terms of cartilage tissue regeneration from chondrocytes, by which chondrocyte phenotypic and molecular characteristics can be retained through the modulation of senescence, dedifferentiation and oxidative stress. Copyright © 2016 John Wiley & Sons, Ltd.